Aprostocetus chilophagae new species (Hymenoptera: Eulophidae) from South Dakota, with taxonomic notes on A. bromi (Kostjukov) and A. nebraskensis (Girault) - Johnson, Paul J.; Yefremova, Zoya A.; Manuel, Juan; López, Perilla; Yegorenkova, Ekaterina N. (Zootaxa, 2018)
Aprostocetus chilophagae Yefremova and Yegorenkova, new species (Hymenoptera: Eulophidae: Tetrastichinae) is described from eastern South Dakota, U.S.A., and is reported as a parasitoid of the larva of Chilophaga virgati Gagné (Diptera: Cecidomyiidae), an ovule predator of Panicum virgatum. This new species is separated from sympatric A. bromi (Kostjukov) and A. nebraskensis (Girault) by structural morphology and host associations. Aprostocetus bromi was recently recognized from North America as an introduced species from Russia that is a primary parasitoid of the introduced ovule feeding gall midge Stenodiplosis bromicola Marikovskij and Agafonova (Cecidomyiidae) on the invasive grass Bromus inermis. Aprostocetus nebraskensis is a native species that is known as a parasitoid only from S. wattsi Gagné, also an ovule predator on the native prairie grasses Andropogon girardii, Schizachyrium scoparium, and Sorghastrum nutans. Trichacis rufipes Ashmead (Platygastridae) co-occurs with A. chilophagae new species on C. virgati, and a Centrodora sp. (Aphelinidae) may be a hyperparasitoid. The females of A. bromi and A. nebraskensis are redescribed and the males for each species are described for the first time.